RETRACTED: Application of hybrid machine learning algorithm in multi-objective optimization of green building energy efficiency - Zhu, Yi; Xu, Wen; Luo, Wenhong; Yang, Ming; Chen, Hongyu; Liu, Yang (Energy (Oxford), 2025)
This article has been retracted: please see Elsevier policy on article withdrawal (https://www.elsevier.com/about/policies-and-standards/article-withdrawal). This article has been retracted at the request of the Editor-in-Chief. Post-publication, an investigation conducted by the Editor-in-Chief discovered substantial changes in authorship during the submission process of this paper. During revision, one author was removed, and the authors Wenhong Luo and Ming Yang were added to the author list without adequate explanation. Additionally, a change in authorship was requested after acceptance, as well as an unjustified change in the affiliation of one co-author. The Editor-in-Chief does not have confidence that all of the stated authors of the article qualify for authorship and has therefore lost confidence in the validity/integrity of the article and made the decision to retract.